Mg-Zn-Ca Alloys for Hemostasis Clips for Vessel Ligation: In Vitro and In Vivo Studies of Their Degradation and Response - Chang, Yen-Hao (Materials (Basel), 2020)
To control the degradation rate of magnesium (Mg) alloys, chitosan (CHI) and L-glutamic acid (LGA) were used as coatings on Mg-Zn-Ca alloys via dip coating. In this study, either two or seven CHI/LGA layers were applied as a coating on Mg-2.8Zn-0.8Ca alloy (ZX31) and Mg-2.8Zn-0.8Ca hemostasis clips (ZX31 clips). The morphologies, compositions, and surface roughness of the specimens were characterized via scanning electron microscopy, Fourier transform infrared spectroscopy, and surface measurement devices. The degradation rates and behavior of the specimens were evaluated by immersing them in simulated body fluids and by applying these ZX31 clips on rabbits’ uterine tubes for five weeks. The specimen with seven layers (ZX31(CHI/LGA)(7)) exhibited improved corrosion behavior when compared with ZX31 or ZX31(CHI/LGA)(2), with a reduced degradation rate of the Mg alloy in a simulated body environment. In vivo experiments showed that ZX31 clips exhibited good biocompatibilities in each group but could not maintain the clamping function for five weeks. The weight loss of ZX31(CHI/LGA)(7) was significantly lower than that of the other groups. Consequently, it was verified that CHI can be used as a protective layer on a magnesium alloy surface via in vitro and in vivo experiments.